CONTINUITY OF MIDWIFERY CARE WITH REBOZO TECHNIQUE APPLICATION: A CASE REPORT - Siti Patia; Desi Hidayanti; Wiwin Widayani (UNIVERSITAS AIRLANGGA, 2026)
Background: Continuity of midwifery care supports comprehensive monitoring during pregnancy, labor, postpartum, and the neonatal period. Labor pain is a physiological process requiring safe, evidence-based management. The Rebozo technique is a non-pharmacological intervention that may reduce labor pain and improve maternal comfort. This article aims to describe the application of the Rebozo technique within continuity of midwifery care to support maternal and neonatal outcomes. Method: This study used a descriptive case report with continuity of midwifery care approach on one woman during August–October 2025 from the third trimester to six weeks postpartum in a primary midwifery care setting. The Rebozo technique was applied during labor for non-pharmacological pain management. Data were collected through interviews, observations, physical examinations, and documentation review. Labor pain intensity was assessed before and after the intervention using the Face, Legs, Activity, Cry, and Consolability (FLACC) scale. Result: During pregnancy, the woman experienced anemia and received daily iron supplementation of 60 mg with nutritional education. Pubic bone pain was relieved through warm compresses and the Rebozo technique. During labor, Rebozo application reduced the pain scale from 6 to 3, with a labor duration of two hours from onset and healthy maternal and neonatal outcomes. The postpartum period progressed normally, while neonatal physiological conditions were managed through education and breastfeeding support. Conclusion : Continuity of midwifery care enables early detection and management of maternal and neonatal conditions. The Rebozo technique demonstrated a clinically meaningful reduction in labor pain; however, careful application is required during rapid labor progression.